Mood responses to athletic performance in extreme environments - Lane, A. M.; Terry, P. C.; Stevens, M. J.; Barney, S.; Dinsdale, S. L. (Journal of Sports Sciences, 2004)
Competition at elite level can require athletes to perform optimally in extreme environmental conditions. This review focuses on mood responses in such conditions and proposes practical guidelines for those working with athletes. Different environments are considered, including altitude and extreme heat and cold. Performing in extreme heat, cold or at altitude can produce a stress response characterized by increased negative mood and relatively poor performance. Positive adaptations to extreme conditions can be accelerated, but the rate of adaptation appears to be highly individualized. Monitoring mood responses to training under normal conditions provides a basis for identifying the psychological effects of extreme conditions. It is suggested that practitioners carefully monitor the interplay between vigour, fatigue and depressed mood. Reductions in vigour and increases in fatigue are normal responses to hard training, but other aspects of mood disturbance, especially symptoms of depressed mood - however small - may be indicative of a maladaptive response, and practitioners should consider intervening when such symptoms first appear.